Implementasi Manajemen Pelatihan Dalam Meningkatkan Keahlian Peserta Di Balai Latihan Kerja - Fa’iq Muhammad Wildan; Ita Nurmalasari; Muhlil Musolin (Universitas KH. Abdul Chalim Pacet Mojokerto, 2026)
The Vocational Training Center, as a government-organized training institution, plays a strategic role in improving workforce competency through computer training programs. This study aims to analyze the Management of the Computer Training Program at the Roudlotul Falaah Srumbung Magelang Vocational Training Center. The type of research used is descriptive qualitative. The results of the study indicate that; it can be concluded that this program has been implemented through a systematic and integrated management approach. The program's foundation is built through a thorough and data-driven planning process. The effectiveness of this program is then supported by structured organization through appropriate resource allocation, clear delegation of authority, and the preparation of an efficient organizational framework. During the implementation stage, this program runs according to theoretical operational standards so as to be able to build ready-to-use technical competencies effectively. The holistic evaluation aspect, encompassing all management functions and learning components, acts as a quality assurance mechanism and a basis for continuous improvement.